PERLAKUAN AKUNTANSI PENDAPATAN DAN PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PSAK NO.23 PADA PT. REDMEN ENERGI DANICA - Mulia Rahmah, SKom., M.Si.; Winda Winda (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This research was conducted to find out how the Accounting Treatment of Income and Presentation of Financial Statements in accordance with Financial Accounting Standards No. 23 of 2015. The study was conducted at PT Redmen Energi Danica, which is domiciled on Jalan Pejaten Raya No 5E Pejaten Barat Pasar Minggu South Jakarta 12510. The method used for data collection is descriptive qualitative, the data used are obtained from observation, interviews and company documentation. financial data. The results showed that the Danica Energy Reduction Unit during applying the cash basis method in revenue recognition, ie revenue recognized when payments received from customers or cash received. The accounting treatment for the presentation and presentation of the financial statements of PT Redmen Energi Danica is not in accordance with the Statement of Financial Accounting Standards (PSAK) No. 23 of 2015, namely income recognized under the accrual basis method.